Pengaruh Jenis Industri, Ukuran Perusahaan, Kompleksitas Perusahaan Dan Profitabilitas Klien Terhadap Audit Fee - Sanisah Huri; Efrizal Syofyan (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to examine (1) the influence of industry type, company size, company complexity and client profitability on audit fees (2) the influence of industry types on audit fees (3) influence of firm size on audit fees (4) the effect of corporate complexity on audit fees (5) the effect of client profitability on audit fees. Data collection uses a purposive sampling method for manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2013-2017. A total of 34 companies were sampled in this study. Research shows that (1) type of industry, size of company, complexity of the company and client profitability together influence audit fees (2) the type of high profile industry and low profile does not affect the high or low audit fees given (3) the greater the size of a company, the higher the audit fee borne by the client (4) the number of subsidiaries does not affect the high or low audit fees given, and (5) companies that have high profits tend to provide a high audit fee because they are vulnerable to misstatement